Mechanics of Biological Tissue
DOI: 10.1007/3-540-31184-x_14
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanics and Macromechanics of the Tensile Deformation of Nacre

Abstract: Many natural materials exhibit extraordinary combinations of mechanical properties which are achieved through highly tailored and organized hierarchical microstructures. In particular, materials which function as natural body armor, such as mollusk shells, possess a structure with important features and properties at a variety of length scales, from the various constituent building blocks to the overall integrated and synergistic mechanical behavior of their complex assemblies. In this study, the mechanical be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…The response was attributed to the sequential force-induced unfolding of the Lustrin A protein. Qi et al (2005) proposed a hyperelastic model intended to capture the special mechanical behavior exhibited by the Lustrin A protein. Their numerical simulations of tensile extension of representative ARTICLE IN PRESS volume elements (RVEs) of nacre showed that the progressive unfolding of molecules in the organic matrix contributed to macroscopic softening, ensuring larger deformations without catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%
“…The response was attributed to the sequential force-induced unfolding of the Lustrin A protein. Qi et al (2005) proposed a hyperelastic model intended to capture the special mechanical behavior exhibited by the Lustrin A protein. Their numerical simulations of tensile extension of representative ARTICLE IN PRESS volume elements (RVEs) of nacre showed that the progressive unfolding of molecules in the organic matrix contributed to macroscopic softening, ensuring larger deformations without catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the mechanics of the molecular rearrangements of proteins in natural materials have been studied by Qi et al (2004Qi et al ( , 2005, and serrated stress-strain curves have been shown to result from kinking and related mechanisms during the deformation of proteins. Buehler and Ackbarow (2007); Buehler et al (2008) have written about modeling the deformation and failure mechanisms, and the importance of elasticity in biological structures.…”
Section: Dissipation Of Energy-beyond Fracture Toughnessmentioning
confidence: 99%
“…The remarkable mechanical properties (e.g., low density, strength and toughness) that distinguish biocomposites from common engineering materials have been attributed to their unique architecture [1], which consists of an arrangement of crystalline prisms or platelets [2]- [4], needles [5], [6], columns [7], [8] or rods [9], [10] encapsulated with an organic matrix. In particular, naturally occurring ceramic-based composites are composed of high volume fractions of stiff mineral (e.g., hydroxyapatite or aragonite) surrounded by compliant organic (i.e., polypeptides or polysaccharides) which present weak interfaces [11], [12] to afford structures with remarkable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%